Empowering Computational Thinking through Personalized Robotics: The Odysseus Model - Lagogiannis, George (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This paper presents Odysseus (Ody), a low-cost, 3D-printable, open-source robotics kit designed to support the teaching of programming, algorithms, and data structures across educational levels. Ody features a dual-mode programming environment, block-based coding for beginners, and Python for advanced learners, enabling a smooth progression in computational thinking. To further support novices, Ody introduces tailored abstract blocks that allow educators to adjust both the level of difficulty and the level of abstraction. Building on this, we extend Vygotsky’s Zone of Proximal Development by adding abstraction as a second dimension, and we propose the Dual-Threshold Scaffolding Model. We also introduce the Functional–Pedagogical Mobility Framework, which positions Ody and comparable technologies in terms of mobility. To assess Ody’s educational impact and user acceptance, we conducted an evaluation with learners using a Technology Acceptance Model (TAM)-based questionnaire. The findings indicate strong engagement and positive reception, suggesting that Ody is a flexible and promising platform for computer science education from foundational through advanced levels.